2001
DOI: 10.1161/hh2401.100598
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor-β 1 Modulates Oxidatively Modified LDL–Induced Expression of Adhesion Molecules

Abstract: Abstract-Oxidatively modified LDL (ox-LDL) activates a lectin-like receptor, LOX-1, which results in the expression of adhesion molecules on endothelial surface. We investigated the regulation of the expression of transforming growth factor-␤ 1 (TGF-␤ 1 ) and its receptors by ox-LDL and the functional significance of this interaction with regard to adhesion molecule expression in human coronary artery endothelial cells (HCAECs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 52 publications
1
33
0
2
Order By: Relevance
“…However, interestingly, our results showed a significant correlation between the tubulointerstitial mRNA expression for LOX-1 mRNA and extent of proteinuria (Fig. 4) (22)(23)(24). More recent studies have also reported relationships between high-glucose, Ox-LDL and albuminuria (25,26 …”
Section: Detection Of Lox-1 Mrna By In Situ Hybridizationsupporting
confidence: 63%
“…However, interestingly, our results showed a significant correlation between the tubulointerstitial mRNA expression for LOX-1 mRNA and extent of proteinuria (Fig. 4) (22)(23)(24). More recent studies have also reported relationships between high-glucose, Ox-LDL and albuminuria (25,26 …”
Section: Detection Of Lox-1 Mrna By In Situ Hybridizationsupporting
confidence: 63%
“…We used TGF␤ 1 ACT to up-regulate TGF␤ 1 because previous studies (5,14) have shown that the active moiety of TGF␤ 1 results in significantly greater biological effects than the latent form of TGF␤ 1 ACT . The suggestion of a role of LOX-1 in the biological effects of TGF␤ 1 comes from studies that indicate that TGF␤ 1 influences the pro-inflammatory effect of oxidized low density lipoprotein (12). In these studies, pretreatment of endothelial cells with anti-LOX-1 antibody attenuated the synthesis of TGF␤ 1 in response to oxidized low density lipoprotein.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that TGF␤ 1 can regulate LOX-1 expression in vascular endothelial cells, smooth muscle cells, and monocytes/macrophages (10,11). Another study showed that LOX-1 blockade reduces TGF␤ 1 protein expression in endothelial cells (12). The present study was conducted to examine whether and how LOX-1 mediates TGF␤ 1 -mediated collagen production.…”
mentioning
confidence: 96%
“…Oxidized LDL, for example, is scavenged through LOX-1 (94), which is highly expressed in blood vessels in hypertension, diabetes, and dyslipidemia (95). Oxidized LDL uptake by LOX-1 triggers a variety of actions: It reduces eNOS expression (96) and further stimulates adhesion molecule expression (97). LOX-1 expression can be stimulated by Ang II and endothelin-1 (98,99).…”
Section: Pathophysiologic Effects Of Endothelial Dysfunctionmentioning
confidence: 99%